The impact of statin use on short-term and long-term mortality in patients with heart failure - Zheng, Xiaoxue; Tan, Long; Zhang, Yu (Frontiers in Pharmacology, 2024)
Background Heart failure (HF) is a complex disorder that has an association with increased morbidity and mortality rates globally. The association of statin use with mortality rate in individuals with HF remains unclear. Objectives To examine the association of statin use with the short-term and long-term all-cause mortality rate in critically ill individuals with HF. Methods We performed a retrospective cohort analysis based on the Medical Information Mart for Intensive Care (MIMIC)-IV database. The critically ill people with HF were assigned to a statin group and a non-statin group according to whether they had been treated with statin or not during hospitalization. The Kaplan−Meier (KM) method and Cox proportional hazard models were adopted to explore the link between statin administration and the 30-day, 90-day, as well as 1-year mortality rates. To ensure the robustness of the findings, a 1:1 nearest propensity-score matching (PSM) was also performed. Results The current research included 11,381 patients for the final analysis, with 7,561 in the statin group and 3,820 in the non-statin group. After multiple confounders were adjusted, we found that the Cox regression models revealed great beneficial effects of statin therapy on the 30-day, 90-day, as well as 1-year mortality rates among critically ill individuals with HF in the fully adjusted model. PSM also achieved consistent results. After PSM, the risk of mortality reduced by 23% for the 30-day mortality (HR = 0.77, 95%CI: 0.68–0.88, p < 0.001), 16% for the 90-day mortality rate (HR = 0.84, 95%CI: 0.75–0.93, p < 0.001), and 12% for the 1-year mortality rate (HR = 0.88, 95%CI: 0.81–0.97, p = 0.007). Patients treated with rosuvastatin had the greatest reduction in mortality rate. The 30-day, 90-day, and 1-year all-cause mortality rates were remarkably lower in patients who were treated with low-dose statins. Conclusion Our study unveiled that statin use was related to decreased short-term and long-term all-cause mortality rates in critically ill individuals with HF. Rosuvastatin was associated with the greatest reduction of all-cause mortality rates. Low-dose statins can significantly reduce short-term and long-term mortality, while high-dose statins are not significantly correlated with mortality. However, the results are not conclusive and should be interpreted with caution.